2007
DOI: 10.1371/journal.pone.0000420
|View full text |Cite
|
Sign up to set email alerts
|

Whole Cell Cryo-Electron Tomography Reveals Distinct Disassembly Intermediates of Vaccinia Virus

Abstract: At each round of infection, viruses fall apart to release their genome for replication, and then reassemble into stable particles within the same host cell. For most viruses, the structural details that underlie these disassembly and assembly reactions are poorly understood. Cryo-electron tomography (cryo-ET), a unique method to investigate large and asymmetric structures at the near molecular resolution, was previously used to study the complex structure of vaccinia virus (VV). Here we study the disassembly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 42 publications
3
44
0
1
Order By: Relevance
“…The structure of many cellular objects that had previously been observed by means of conventional EM has been reinterpreted, new structural motifs have been found, and prevailing paradigms are being challenged. Applied to large molecular assemblies, EMT has provided invaluable insights into the structure of the ribosome (Zhao et al, 2004a, b), proteosome (Böhm et al, 2000;Medalia et al, 2002), flagellar motors (Nicastro et al, 2005;Murphy et al, 2006), nuclear pore complexes (Stoffler et al, 2003;Beck et al, 2007) and viruses Cyrklaff et al, 2007;Subramaniam et al, 2007;Dai et al, 2008). It has likewise been instrumental in revealing the intricate organization of complex, pleiomorphic structures, which impede high resolution 3D analysis by other methods, such as the cytoskeleton, in eukaryotes (Kurner et al, 2004;Hoog and Antony, 2007;O'Toole et al, 2007;Koning et al, 2008;Perkins et al, 2008) and in prokaryotes (Scheffel et al, 2006;Jensen and Briegel, 2007), and the spindle pole body of yeast (O'Toole et al, 1999;Melloy et al, 2007).…”
Section: Techniques In Electron Microscopy Of Plant Samplesmentioning
confidence: 99%
“…The structure of many cellular objects that had previously been observed by means of conventional EM has been reinterpreted, new structural motifs have been found, and prevailing paradigms are being challenged. Applied to large molecular assemblies, EMT has provided invaluable insights into the structure of the ribosome (Zhao et al, 2004a, b), proteosome (Böhm et al, 2000;Medalia et al, 2002), flagellar motors (Nicastro et al, 2005;Murphy et al, 2006), nuclear pore complexes (Stoffler et al, 2003;Beck et al, 2007) and viruses Cyrklaff et al, 2007;Subramaniam et al, 2007;Dai et al, 2008). It has likewise been instrumental in revealing the intricate organization of complex, pleiomorphic structures, which impede high resolution 3D analysis by other methods, such as the cytoskeleton, in eukaryotes (Kurner et al, 2004;Hoog and Antony, 2007;O'Toole et al, 2007;Koning et al, 2008;Perkins et al, 2008) and in prokaryotes (Scheffel et al, 2006;Jensen and Briegel, 2007), and the spindle pole body of yeast (O'Toole et al, 1999;Melloy et al, 2007).…”
Section: Techniques In Electron Microscopy Of Plant Samplesmentioning
confidence: 99%
“…1a) recorded and computed in the same conditions as in the whole cell approach [1]. We surprisingly found that the major changes to the vaccinia structure happen right before the internalization into the host cell cytoplasm [5]. This is the stage when the virus interacts with receptors exposed on the host cell plasma membrane.…”
Section: Vaccinia Virus Infected Cellsmentioning
confidence: 91%
“…This generally limits the type of specimens that can be imaged by EM to isolated viruses (Hong et al, 2015;Murata et al, 2010;Dai et al, 2010), protein complexes (Koyfman et al, 2011;Nickell et al, 2007a,b), organelles (Eibauer et al, 2015;Nicastro et al, 2000;Beck et al, 2007Beck et al, , 2004, smaller prokaryotic cells (Briegel et al, 2015;Zhao et al, 2014) and thin peripheral regions of eukaryotic cells (Hu, 2014;Ben-Harush et al, 2010;Patla et al, 2010;Cyrklaff et al, 2007). Cells up to 1 μm in thickness can be imaged by EM, as shown for Ostreococcus tauri, the smallest eukaryotic cell (Henderson et al, 2007); this has provided a unique insight into the ultrastructure and characteristics of the cells during different stages of their cell cycle.…”
Section: Improved Em Optics Impact On What We See Inside the Cellmentioning
confidence: 99%